2000
DOI: 10.1677/joe.0.1660609
|View full text |Cite
|
Sign up to set email alerts
|

Altered chicken thyroid hormone metabolism with chronic GH enhancement in vivo: consequences for skeletal muscle growth

Abstract: In contrast to most vertebrates, GH reportedly has no effect upon somatic growth of the chicken. However, previous studies employed only one to two dosages of the hormone, and limited evidence exists of a hyperthyroid response that may confound its anabolic potential. This study evaluated the effects of 0, 10, 50, 100 and 200 µg/kg body weight per day chicken GH (cGH) (0-200 GH) infused i.v. for 7 days in a pulsatile pattern to immature, growing broiler chickens (9-10 birds/dosage). Comprehensive profiles of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Vasilatos et al (2000) reported that GH injection decreased the deposition of breast muscle and the leg muscle of broilers, which may be differences of sensitivity of muscle fiber types. Color is one of the main characteristics of meat quality, which is determined by myoglobin content that depends on the myofibril types in muscle.…”
Section: Discussionmentioning
confidence: 98%
“…Vasilatos et al (2000) reported that GH injection decreased the deposition of breast muscle and the leg muscle of broilers, which may be differences of sensitivity of muscle fiber types. Color is one of the main characteristics of meat quality, which is determined by myoglobin content that depends on the myofibril types in muscle.…”
Section: Discussionmentioning
confidence: 98%
“…Together these alterations in deiodination result in the perihatch T 3 peak (see "Deiodination Enzymes" earlier in this article). The effects of GH on 5D III also are present in immature growing broiler chickens (Vasilatos-Younken et al, 2000). Glucocorticoids, which also may influence deiodinases, increase late in incubation/gestation, but in contrast to mammals, they appear not to be an important factor in the changes in deiodination activity at this time in precocial birds (see review in Darras et al, 1995).…”
Section: Effects On Growth Interactions Between the Thyroid And Growtmentioning
confidence: 99%
“…Plasma concentrations of GH were elevated in a dosedependent fashion with GH infusion, and ranged from 0·3 5·7 ng/ml for controls up to 89·0 5·4 ng/ml at the highest dosage (200 µg/kg BW per day) (for detailed profile see Vasilatos-Younken et al 2000). Plasma GH concentrations for pair-fed groups did not differ from controls (Table 1).…”
Section: Effects Of Pulsatile Cgh Infusion On Circulating Gh and Fimentioning
confidence: 93%